Design and construction of a 1.8 K superfluid 4He system with a G-M cryocooler. (September 2019) - Li, Xu; Xu, Dong; Wang, Wei; Lin, Peng; Liu, Huiming; Nishimura, Arata; Shen, Fuzhi; Li, Laifeng
Highlights: A superfluid 4 He production system with a G-M cryocooler has been developed to obtain continuous cooling capacity. Continuous operation with small temperature oscillation at 1.78 K has been demonstrated. The influence caused by the change of 4 He gas flow rate and pressure in the He I pot can be reduced. Abstract: This paper describes a superfluid 4 He (He II) production system with a G-M cryocooler developed to supply continuous cooling capacity for cryogenic devices working below 2 K, such as the sealed-cell lambda-point devices and the photon detectors. Unlike the existing cooling method that injecting and pumping liquid 4 He (He I) to cool the devices, high purity 4 He gas stored in gas cylinder is firstly liquefied by a G-M cryocooler in the condenser, and then cooled down under 2.17 K at the He II pot through a Joule-Thomson valve along with a dry vacuum pump. This design allows a continuous supplement of He II below 2.17 K by using 4 He at ambient temperature, which avoids the temperature oscillation to the devices being cooled when refilling He I. Due to the removing of cryogen injection, no additional cryogenic apparatus and professional operation are required. In this system, the He II pot can reach a temperature below 1.8 K for continuous operation.